2016
DOI: 10.3109/10826084.2015.1133646
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Varenicline for Smoking Cessation in Psychiatric and Addicts Patients

Abstract: Gastrointestinal adverse events are the most incident in this sample of psychiatric patients and no exacerbation of psychiatric symptoms was detected, thus indicating a good safety record for varenicline use for smoking cessation in psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…The adverse events observed in the psychiatric disorder group in our sample were: dry mouth, flatulence, abnormal dreams, and nausea. According to diagnostic groups, the patients using methadone presented more adverse events than the alcohol group, but we did not observe other significant differences across diagnostic groups 22 . In our previous study, we reported that reducing the dose to 1 mg/day improved treatment adherence in patients who experienced adverse events and we also found that varenicline did not induce any significant exacerbations of psychiatric symptoms 22 .…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…The adverse events observed in the psychiatric disorder group in our sample were: dry mouth, flatulence, abnormal dreams, and nausea. According to diagnostic groups, the patients using methadone presented more adverse events than the alcohol group, but we did not observe other significant differences across diagnostic groups 22 . In our previous study, we reported that reducing the dose to 1 mg/day improved treatment adherence in patients who experienced adverse events and we also found that varenicline did not induce any significant exacerbations of psychiatric symptoms 22 .…”
Section: Resultscontrasting
confidence: 83%
“…Our team assessed the safety of varenicline in a previous study 22 . In the present study, we again evaluated safety, finding that varenicline was safe in this sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 49 In a prospective longitudinal study among psychiatric patients, there was no exacerbation of psychiatric symptoms detected except gastrointestinal adverse events. 50 However, although it is not within the scope of this study, what need to be mentioned is that an increased rate of outpatient visits for schizophrenia was previously reported to be present only in patients with a pre-existing mental health disorder. 32 This may be explained by mediation through individual genetic liability.…”
Section: Main Findings and Interpretationmentioning
confidence: 79%
“…Furthermore, the model does not include possible costs or effects of adverse events of varenicline. However, recent studies have not shown an adverse safety profile for varenicline 57, 58, 59, 60, 61, 62. Close collaboration with stakeholders and experts in the field of smoking cessation both nationally and internationally allowed us to evaluate interventions for which no effectiveness data could be identified for Germany.…”
Section: Discussionmentioning
confidence: 99%